Analysis of Outcomes in Adolescents and Young Adults With Pilonidal Disease - Abraham, Mackenzie N.; Raymond, Steven L.; Hawkins, Russell B.; Iqbal, Atif; Larson, Shawn D.; Mustafa, Moiz M.; Taylor, Janice A.; Islam, Saleem (Frontiers in Surgery, 2021)
Purpose: Numerous definitive surgical techniques exist for the treatment of pilonidal disease with varied recurrence rates and wound complications. Due to the wide array of techniques and lack of consensus on the best approach, we proposed to study our experience treating pilonidal disease in adolescents and young adults. Methods: A retrospective analysis was conducted of patients 10-24 years old treated at a tertiary medical center from 2011-2016. Data including demographics, management, and outcomes were collected and analyzed. Primary outcome was recurrence of disease. Results: 133 patients with pilonidal disease underwent operative management. 51% underwent primary closure and 49% healed by secondary intention with no significant difference in recurrence rates (primary 18%, secondary 11%; p=0.3245). Secondary healing patients had significantly lower wound complication rates (primary 51%, secondary 23%; p=0.0012). After accounting for sex, race, weight, and operative technique, age was predictive of disease recurrence with an adjusted odds ratio (OR) of 0.706 (0.560-0.888; p=0.003). Age and sex were both predictive of wound complications. Older patients had decreased risk of wound complication (adjusted OR 0.806, 95% CI 0.684-0.951; p=0.0105), and male patients had increased risk of wound complication (adjusted OR 2.902, 95% CI 1.001-8.409; p=0.0497). Conclusion: In summary, there is no significant difference in the recurrence rates between operative techniques for pilonidal disease. Older patients have decreased risk of recurrence following intervention. Wound complication rates are lower in patients undergoing secondary healing, though this may be better explained by differences in age and sex. Additional research investigating newer, minimally-invasive techniques needs to be pursued.